Temperature dependency of Cu/Zn ordering in CZTSe kesterites determined by anomalous diffraction. Issue 10 (28th July 2016) - Többens, Daniel M.; Gurieva, Galina; Levcenko, Sergiu; Unold, Thomas; Schorr, Susan
Abstract : Low‐temperature cation ordering is emerging as a critical factor limiting the efficiency of CZTSSe kesterite photovoltaic materials. By means of direct determination of the site occupancies from anomalous X‐ray powder diffraction data at the Cu‐ and Zn‐absorption edges, the ordering of Cu + and Zn 2+ in B‐type Cu2 ZnSnSe4 (CZTSe) kesterite upon annealing at temperatures below 203 (6) °C is demonstrated. Anomalous X‐ray diffraction on the Cu‐ and Zn‐K absorption edges allows determination of the distribution of isoelectric Cu 1+ and Zn 2+ over the crystallographic sites in a B‐type CZTSe kesterite (Cu1.949(20) Zn1.059(10) Sn0.983(10) Se4 ) powder. By Rietveld refinement the quantitative determination of both Cu‐ and Zn‐occupancy for all relevant sites is achieved. From this, the temperature dependency of a structure‐based, quantitative order parameter is determined. The critical temperature of the phase transition is confirmed at 203 (6) °C. The ordering mechanism is in agreement with a transition from disordered to ordered kesterite. The photoluminescence band maximum shows a closely related temperature dependency, directly demonstrating the effect of cation ordering on the optical properties of CZTSe.